Banisteriopsis caapi, a unique combination of MAO inhibitory and antioxidative constituents for the activities relevant to neurodegenerative disorders and Parkinson’s disease - Samoylenko, Volodymyr (2009)
AIM OF THE STUDY: Parkinson’s disease is a neurological disorder mostly effecting the elder population of the world. Currently there is no definitive treatment or cure for this disease. Therefore, in this study the composition and constituents of the aqueous extract of B. caapi for monoamine oxidases (MAO) inhibitory and antioxidant activities were assessed, which are relevant to the prevention of neurological disorders, including Parkinsonism. MATERIALS AND METHODS: The aqueous extract of B. caapi stems was standardized and then fractionated using reversed-phase (RP) chromatography. Pure compounds were isolated either by reversed-phase (RP) chromatography or centrifugal preparative TLC, using a Chromatotron(®). Structure elucidation was carried out by 1D and 2D NMR, Mass, IR and Circular Dichroism spectroscopy and chemical derivatization. Chemical profiling of the extract was carried out with RP-HPLC. The inhibitory activity of MAO-A, MAO-B, acetylcholinesterase, butyrylcholinesterase and catechol-O-methyl transferase enzymes, as well as antioxidant and cytotoxic activities of both B. caapi extract and isolated compounds were evaluated. RESULTS: An examination of the aqueous extracts of B. caapi cultivar Da Vine yielded two new alkaloidal glycosides, named banistenoside A (1) and banistenoside B (2), containing “azepino[1,2-a]tetrahydro-β-carboline” unique carbon framework. One additional new natural tetrahydronorharmine (4), four known β-carbolines harmol (3), tetrahydroharmine (5), harmaline (6) and harmine (7), two known proanthocyanidines (−)-epicatechin (8) and (−)-procyanidin B2 (9), and a new disaccharide β-D-fructofuranosyl-(2→5)-fructopyranose (14) together with known sacharose (15) and β-D-glucose (16) were also isolated. In addition, the acetates of 1, 2, 8, 9, 14 and 15 (compounds 10–13, 17, 18) were also prepared. Harmaline (6) and harmine (7) showed potent in vitro inhibitory activity against recombinant human brain monoamine oxidase (MAO) -A and -B enzymes (IC(50) 2.5 and 2.0 nM, and 25 and 20 µM, respectively), and (−)-epicatechin (8) and (−)-procyanidin B2 (9) showed potent antioxidant and moderate MAO-B inhibitory activities (IC(50) <0.13 and 0.57 µg/mL, and 65 and 35 µM). HPLC analysis revealed that most of the dominant chemical and bioactive markers (1, 2, 5, 7–9) were present in high concentrations in dried bark of large branch. Analysis of regular/commercial B. caapi dried stems showed a similar qualitative HPLC pattern, but relatively low content of dominant markers 1, 2, 7, and 9, which led to decreased MAO inhibitory and antioxidant potency. CONCLUSION: Collectively, these results give additional basis to the existing claim of B. caapi stem extract for the treatment of Parkinsonism, including other neurodegenerative disorders.